Multi-Beam Type LINAC for HIF Injector - Lu, Liang; Ma, Wei; lei, Yang; He, Tao; Sun, Liepeng; He, Yuan; Zhao, Hongwei (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
The very high intense heavy-ion beam is a high attraction for heavy ion researches and heavy-ion applications, but it is limited by heavy-ion production of existing ion source and space-charge-effect in acceleration. There is one way, accelerating several heavy-ion beams in one cavity at same time and funneling them, which could achieve the acceleration of very high intense heavy-ion beam with existing ion source and accelerating technology...
Keywords: multi-beam type LINAC; HIF injector